65 lat działu socjologicznego „Ruchu" - Włodarczyk, Dorota (Wydział Prawa i Administracji UAM, 1992)
The article sketches the history of the sociological division of „Ruch Prawniczy. Ekonomiczny i Socjologiczny". The author presents the founders of the periodical, its editorial arrangement over the years, as well its authors and subjectmatter characterization of the periodical. She also includes qualitative and quantitative evaluation and statistics concerning the authors and publications of the Periodical.
Sixty-five years of sociological division of „Ruch Prawniczy, Ekonomiczny i Socjologiczny"